Addressing stray animal population through alteration of sex ratio - Shukla, M. K.; Kumar, Rajesh (Animal Reproduction Update, 2022)
Livestock plays a significant role in rural economy and livelihood by providing milk, meat, hide, drought power, etc. India’s livestock sector is one of the largest in the world with a holding of 11.6% of world livestock population. But due to economic reasons, dairy farmers have a strong preference for female calves for milk production and hence there is a very limited demand for male calves. Apart from that, there are several other reasons such as negligence of the indigenous populations and excessive focus on crossbreeding in the past few decades, increased mechanisation and the national policy to ban on cow slaughter have further added to the problem. In the common parlance, stray cattle include low-yield cows, bulls or calves that are abandoned and free to roam about in the open during the daytime because they are unproductive and creating traffic nuisance in cities, they also attack crops in villages. Therefore, techniques for gender selection and skewing of sex ratio towards female are demand of the hour. Flow cytometric sorting of spermatozoa is one of the best approaches to select the sexed semen for desire sex of calf, but its cost and patented technology is a definite disadvantage of this technology. In the present review, we will discuss in detail about the techniques available for skewing of sex ratio to address the stay animal population.